2002
DOI: 10.1016/s0014-5793(02)02232-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functional VEGF receptors on human platelets

Abstract: Platelets secrete platelet-derived growth factor (PDGF) and vascular endothelial growth factor (VEGF) upon stimulation. We have demonstrated that platelets have functionally active PDGF K K-receptors, a transmembrane tyrosine kinase involved in negative feedback regulation. Here we demonstrate the presence of the related VEGF receptors fms-like tyrosine kinase-1 and kinase-insert domain region on human platelets. VEGF itself did not cause platelet aggregation. However, addition of exogenous VEGF to SFRLLN or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 25 publications
2
42
0
1
Order By: Relevance
“…In addition, platelets also contain cryptic VEGF receptors, including KDR, which become exposed on the platelet membrane upon stimulation by VEGF. 26 Although it can be argued that platelets are readily discerned by their size and the absence of a nucleus, this assumption is fundamentally flawed if platelet proteins can be transferred to other cell types. 27 After platelet activation, a myriad of platelet MPs accumulates at sites of tissue injury and leaks into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, platelets also contain cryptic VEGF receptors, including KDR, which become exposed on the platelet membrane upon stimulation by VEGF. 26 Although it can be argued that platelets are readily discerned by their size and the absence of a nucleus, this assumption is fundamentally flawed if platelet proteins can be transferred to other cell types. 27 After platelet activation, a myriad of platelet MPs accumulates at sites of tissue injury and leaks into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Both receptors are expressed on subsets of hematopoietic cells such as hematopoietic stem cells, monocytes, and platelets for VEGFR-1 (43,51) and hematopoietic stem cells, endothelial progenitors, and platelets for VEGFR-2 (10,51). This overlap in VEGF receptor expression makes it difficult to specifically study the role of each individual receptor.…”
Section: Vegfr-2 Signaling In Hematopoietic Progenitorsmentioning
confidence: 99%
“…VEGF expression is upregulated in the majority of human tumours, where it stimulates proliferation, migration and survival of endothelial cells by binding to two high-affinity tyrosine kinase receptors, VEGFR-1/Flt-1 and VEGFR-2/KDR. VEGF receptors (VEGFRs) are mainly expressed by endothelial cells, although they have also been detected in other cell types, including macrophages, monocytes (1) and platelets (2). More recently, it was shown that both VEGF and its receptors are expressed in haematological (3), pancreatic (4) and prostatic (5) tumour cells, where they may serve as autocrine stimulators of proliferation, migration and survival.…”
Section: Introductionmentioning
confidence: 99%